Correlation of single nucleotide polymorphisms in the promoter region of the ANXA5 (annexin A5) gene with recurrent miscarriages in women of Greek origin. (2nd May 2020) - Dryllis, G.; Giannopoulos, A.; Zoi, C.; Pouliakis, A.; Logothetis, E.; Voulgarelis, M.; Zoi, K.; Kouskouni, E.; Dinou, A.; Stavropoulos-Giokas, C.; Kreatsas, G.; Konstantopoulos, K.; et al.
Abstract: Background: Recent findings show that a number of single nucleotide polymorphisms (SNPs) within the promoter region of the annexin A5-gene (ANXA5) reduce the expression of the reporter gene and so they display a significant association with recurrent pregnancy loss (RPL). Objective: The objective of the present study aimed to address the contribution of ANXA5 M2 haplotype consisting of four minor alleles: (SNP1: (−)467G > A, SNP2: (−)448A > C, SNP3: (−)422T > C, and SNP4: (−)373G > A) in the occurrence of recurrent pregnancy losses in the Greek population, and the role of further two minor alleles: SNP5: (−)302 T > G and SNP6: (−)1C > T as independent risk factors for RPL. Methods: A 752-bp genomic region of ANXA5 promoter was amplified by PCR using specific primers. Genotypic analysis by Sanger sequencing was performed for these six SNPs (minor alleles) in the promoter region of ANXA5 gene, in 100 (100) Greek women with recurrent miscarriages (median =3) and 70 (70) fertile controls. Statistical analysis was done using the SAS 9.3 for Windows (SAS Institute Inc, NC, USA) and SPSS packages for Windows (C.DiMaggio 2013, SAS Institute 2014). Results: This case-control study revealed that there is no significantly increased risk of RPL among the M2/ANXA5 haplotype carriers in the Greek population, as there were no statistical differences between the patients with recurrent pregnancy losses and the fertile controls (11.5% in RPL cases versus 9.29% in controls, p -value: .6364). There was no difference in SNP5 and SNP6 minor carriership between the two groups. In particular, carriers of SNP5 and SNP6 had an increased risk for RPL state with odds ratio: 1.2472 and 1.3846 respectively, however without statistically significant importance. Conclusion: The M2/ANXA5 haplotype does not differ between RPL patients and controls in the Greek population. Also, it is the first time that SNP5 and SNP6 minor alleles were evaluated extensively in women of European origin with recurrent pregnancy losses (RPL), and they do not seem to be independent risk factors in the occurrence of RPL in the Greek population. Though, this has to be confirmed in further and larger clinical trials with women of European origin.